The presence and development of the National Liberation Front’s authority among Algerian immigrants in Morocco and winning the struggle for international legitimacy. - Fawzi, ferahtia; lamiche, salah (Journal of Social Sciences and Humanities, 2021)
This study seeks a serious and purposeful attempt aimed at standing at one of the most important events that formed a challenge to the Algerian revolution through its conflict with the French colonialism, both; inside through the armed struggle or abroad through the war of diplomatic propaganda to win the battle of betting on refugees, especially the neighboring countries, those who were forming ;before the starting of the revolution, the category of Algerian immigrants in the Morocco, which is the most important aspect of our study, and then their number doubled with the outbreak of the Algerian revolution due to the policy of colonial repression and forced displacement of the people who lived in villages and towns across the border areas. Therefore the FLN tried to convince and adapt them because they were the basis of the strategic revolution in the Morocco. This category will form another conflict with the French colonialism authorities represented in its diplomacy and consulate located in Morocco, which insisted that their affair should not be internationalized and that they are considered as citizens of "French Muslims" who were pushed by "violence" to leave their country, and between the propaganda of the colonial system that did not leave any way to emphasize on they are refugees forced into this conflict by the policy of colonial repression, supported by the efforts of the Red Crescent, which also entered the battle to win the refugee issue in the ranks of humanitarian agencies and organizations.